Prophylactic management of cerebral vasospasm with clazosentan in real clinical practice: a single-center retrospective cohort study - Sakata, Hiroyuki; Kanoke, Atsushi; Uchida, Hiroki; Haryu, Shinya; Omodaka, Shunsuke; Kimura, Naoto; Yoshida, Masahiro; Niizuma, Kuniyasu; Tominaga, Teiji; Endo, Hidenori (Frontiers in Neurology, 2024)
Introduction Clazosentan, a selective endothelin receptor subtype A antagonist, reduces vasospasm-related morbidity and all-cause mortality following aneurysmal subarachnoid hemorrhage (SAH) in the Japanese population, as demonstrated by a recent randomized phase 3 trial. However, evidence to suggest clazosentan should be prioritized over the current standard of care to prevent cerebral vasospasm is still lacking. Therefore, we investigated the efficacy and safety of clazosentan in comparison with conventional postoperative management in real-world clinical practice. Methods We conducted a single-center, retrospective, observational cohort study using prospectively collected data from consecutive patients with aneurysmal SAH. After clazosentan was approved for use in Japan, the conventional postoperative management protocol, composed of intravenous fasudil chloride and oral cilostazol (control group, April 2021 to March 2022), was changed to the clazosentan protocol (clazosentan group, April 2022 to March 2023). The primary endpoint was the incidence of vasospasm-related symptomatic infarction. The secondary endpoints were favorable functional outcomes (modified Rankin scale score < 3) at discharge, angiographic vasospasm, and the need for rescue therapy for delayed cerebral ischemia. Results The analysis included 100 and 81 patients in the control and clazosentan groups, respectively. The incidence of vasospasm-related symptomatic infarction was significantly lower in the clazosentan group than in the control group (6.2% vs. 16%, p = 0.032). Multiple logistic analyses demonstrated that the use of clazosentan was independently associated with fewer incidence of vasospasm-related symptomatic infarct (23.8% vs. 47.5%, odds ratio 0.34 [0.12–0.97], p = 0.032). Clazosentan was significantly associated with favorable outcomes at discharge (79% vs. 66%, p = 0.037). Moreover, both the incidence of angiographic vasospasm (25.9% vs. 44%, p = 0.013) and the need for rescue therapy (16.1% vs. 34%, p = 0.006) was lower in the clazosentan group. The occurrence of pulmonary edema was significantly higher with clazosentan use (19.8% vs. 5%, p = 0.002), which did not result in morbidity. Conclusion A postoperative management protocol centering on clazosentan was associated with the reduced vasospasm-related symptomatic infarction and improved clinical outcomes compared to the conventional management protocol in Japanese clinical practice. Clazosentan might be a promising treatment option for counteracting cerebral vasospasm after aneurysmal SAH.